Evaluation of the effects of essential oil extracted from sweet orange peel (Citrus sinensis) on growth rate of tilapia (Oreochromis mossambicus) and possible disease resistance against Streptococcus iniae - Acar, Ümit; Kesbiç, Osman Sabri; Yılmaz, Sevdan; Gültepe, Nejdet; Türker, Ali (Elsevier BV, 2015)
Abstract The study was performed to determine the effect of dietary essential oil (citrus EO) extracted from sweet orange peel (Citrus sinensis) on growth performance, blood parameters and resistance against the Streptococcus iniae in Mozambique tilapia (Oreochromis mossambicus). Fish were divided into 4 groups and fed for 90 days with four experimental diets (3 supplemented diets with 0.1%, 0.3%, and 0.5% of citrus EO and a control group). Then the main immune parameters such as lysozyme and myeloperoxidase activity, hematological and biochemical variables (i.e., hemoglobin, hematocrit levels, erythrocyte indices, serum total protein, glucose, albumin, globulin, cholesterol and triglyceride) were investigated. Results of this study showed that for tilapia fed with citrus EO all parameters were significantly higher than the control group. Moreover, addition of citrus EO into diets reduced fish mortality after S. iniae infection. It can be concluded that citrus EO can act as a growth promoter, increase immunity and also improve disease resistance to S. iniae infection in tilapia. Thus it can be used as an antibiotics replacer for controlling diseases in tilapia feed.
Keywords: 2. Zero hunger; 10. No inequality; 3. Good health